Computer-aided drug design for virtual-screening and active-predicting of main protease (Mpro) inhibitors against SARS-CoV-2 - Dai, Renhui; Gao, Hongwei; Su, Ruiling (Frontiers in Pharmacology, 2023)
SARS-CoV-2 is a novel coronavirus with highly contagious and has posed a significant threat to global public health. The main protease (M pro ) is a promising target for antiviral drugs against SARS-CoV-2. In this study, we have used pharmacophorebased drug design technology to identify potential compounds from drug databases as M pro inhibitors. The procedure involves pharmacophore modeling, validation, and pharmacophore-based virtual screening, which identifies 257 compounds with promising inhibitory activity. Molecular docking and non-bonding interactions between the targeted protein M pro and compounds showed that ENA482732 was the best compound. These results provided a theoretical foundation for future studies of M pro inhibitors against SARS-CoV-2.